A tendril perversion in a helical oligomer: trapping and characterizing a mobile screw-sense reversal. Issue 4 (15th February 2017) - Tomsett, Michael; Maffucci, Irene; Le Bailly, Bryden A. F.; Byrne, Liam; Bijvoets, Stefan M.; Lizio, M. Giovanna; Raftery, James; Butts, Craig P.; Webb, Simon J.; Contini, Alessandro; Clayden, Jonathan
Abstract : Inducing opposite screw senses at the two ends of a helix traps a helix reversal, allowing it to be characterised spectroscopically. Abstract : Helical oligomers of achiral monomers adopt domains of uniform screw sense, which are occasionally interrupted by screw-sense reversals. These rare, elusive, and fast-moving features have eluded detailed characterization. We now describe the structure and habits of a screw-sense reversal trapped within a fragment of a helical oligoamide foldamer of the achiral quaternary amino acid 2-aminoisobutyric acid (Aib). The reversal was enforced by compelling the amide oligomer to adopt a right-handed screw sense at one end and a left-handed screw sense at the other. The trapped reversal was characterized by X-ray crystallography, and its dynamic properties were monitored by NMR and circular dichroism, and modelled computationally. Raman spectroscopy indicated that a predominantly helical architecture was maintained despite the reversal. NMR and computational results indicated a stepwise shift from one screw sense to another on moving along the helical chain, indicating that in solution the reversal is not localised at a specific location, but is free to migrate across a number of residues. Analogous unconstrained screw-sense reversals that are free to move within a helical structure are likely to provide the mechanism by which comparable helical polymers and foldamers undergo screw-sense inversion.